Diseño de una cámara frigorífica para quesos en la microempresa de productos lácteos “Don Pato" - Cajas Caillagua, Jhoffre Oswaldo (2022)
This project refers to the design of a cold store for the “Don Pato” dairy microenterprise, taking into consideration that it does not have adequate refrigeration equipment, so its production is currently limited, having as products cheeses of three amplitude. Therefore, to carry out this design, a bibliographical investigation begins to determine and know the requirements of the equipment and materials that make up a cold store at the national level. In addition, an in-situ inspection is required to obtain border parameters such as the conservation temperature at which the cheeses are kept, the production of the microenterprise and what dimensions are available in terms of the location area. Through the compilation of the border parameters, the separated ones were made to determine the type of equipment and materials that should be taken into consideration for the cold store design. Also, it was determined the behavior in terms of the temperature conservation that the cold storage will have, which is 4 °C. In addition, it was determined that the compressor should have a power of 1.29 kW, evaporator 15766.03 BTU / h, condenser 573.08 BTU / h, refrigerant R404 A and polyurethane is 60 mm thick. Finally, a CAD software was produced to draw the cold storage and thus be able to visualize the isometric model that could be implemented in the future in the “Don Pato! dairy microenterprise. However, once the 3D modeling was done, results of the internal temperature behavior in the cold storage were obtained with the help of CAE software.